Reforma vídeňských feniků Maxmiliána I. na počátku 16. století a její vliv na měnový systém českých zemí - Petr Vorel (Theatrum Historiae)
In his contribution, the author explains the reasons why in the course of the 16th century, there were two cases in the Czech lands of minting the so-called Viennese pfennig (farthing), representing the smallest coin in the Austrian currency system. The first case of minting of this tender was in Kłodzko by the counts of Hardegg in the years 1508-1513, while the second case of minting of the Austrian pfennig was in the government mint in Wrocław in Silesia in the years 1540-1541. The author explains these two anomalies of the Czech currency system of the 16th century in connection with the currency reform of smaller coinage in Austrian states, carried out at the beginning of the 16th century by Maxmilian I.